Knowledge management as a key process for business and academic improvement - Gallego Duque , Nicolás Augusto (2022)
In recent years, knowledge management (KM) has become an essential tool that, when well executed and administered within business and academic organizations, produces important dividends. This paper was to show the importance of KM in companies and universities as a tool that contributes to improving results and solving problems. The research followed a qualitative methodology, and a literature review was conducted based on top-level papers. Information was collected according to three criteria: evolution of KM trends, importance of KM in business and academia, and KM measurement models. Axial coding was used to group the information into categories or topics. The most noteworthy findings show that KM has brought about changes that range from improvements in the economy to continuous transformations in society and business. An important conclusion is that KM in universities helps to meet social demands in a more efficient way and, in companies, adds value through the fulfillment of the core purposes.